2019
DOI: 10.1002/ijc.32152
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal pathogens are a risk factor of oral cavity squamous cell carcinoma, independent of tobacco and alcohol and human papillomavirus

Abstract: Over the past decade, there has been a change in the epidemiology of oral cavity squamous cell cancer (OC‐SCC). Many new cases of OC‐SCC lack the recognized risk factors of smoking, alcohol and human papilloma virus. The aim of this study was to determine if the oral microbiome may be associated with OC‐SCC in nonsmoking HPV negative patients. We compared the oral microbiome of HPV‐negative nonsmoker OC‐SCC(n = 18), premalignant lesions(PML) (n = 8) and normal control patients (n = 12). Their oral microbiome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 44 publications
(81 reference statements)
11
149
1
3
Order By: Relevance
“…Although in healthy humans the Prevotella genus is one of the dominant genera of the salivary microbiome, distinct members of the genus Prevotella are associated with inflammatory diseases and may facilitate carcinogenesis as well [86-88, reviewed by 89,90]. There are, however, contradicting observations regarding the role of Prevotella in the development of oral cancer [14,74,79,[91][92][93][94]. Thus, it remains to be established whether members of the genus Prevotella are opportunistic inhabitants of malignant tumors or play a causative role in oral or colorectal carcinogenesis [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…Although in healthy humans the Prevotella genus is one of the dominant genera of the salivary microbiome, distinct members of the genus Prevotella are associated with inflammatory diseases and may facilitate carcinogenesis as well [86-88, reviewed by 89,90]. There are, however, contradicting observations regarding the role of Prevotella in the development of oral cancer [14,74,79,[91][92][93][94]. Thus, it remains to be established whether members of the genus Prevotella are opportunistic inhabitants of malignant tumors or play a causative role in oral or colorectal carcinogenesis [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…are opportunistic pathogens that cause diverse infections and show strong connections and contributions to multiple diseases in humans and higher mammals (15). F. nucleatum has garnered significant attention as an "oncobacterium" that contributes to the progression and severity of colorectal cancer and has also been implicated in malignant oral leukoplakia (45), oral squamous cell carcinoma (46,47), and pancreatic cancer (48,49). Because F. nucleatum is an oncomicrobe, F. nucleatum infection studies have shown that administration of the antibiotic metronidazole reduces the tumor burden in human tumor-generated xenografts in mice (22).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in oral microbiome may be associated with chronic inflammation such as in periodontitis and lead to malignant transformation of the oral mucosa (19)(20)(21). A recent study has also suggested an association between periodontal pathogens and OSCC in NSND (59).…”
Section: Viral Oncogenesis Of Oscc In Nsnd: Should We Incriminate Onlmentioning
confidence: 99%